Electron and phonon transport properties of layered Bi2O2Se and Bi2O2Te from first-principles calculations - Cong Wang; Guangqian Ding; Xuming Wu; Shasha Wei; Guoying Gao (New Journal of Physics, 2018)
Recent experiments indicated that both layered Bi _2 O _2 Se and Bi _2 O _2 Te are promising thermoelectric materials with low thermal conductivities. However, theoretical study on the thermoelectric properties, especially the phonon transport properties, is rare. In order to understand the thermoelectric transport mechanism, we here investigate the electron and phonon transport properties by using the first-principles calculations combined with the Boltzmann transport theory. Our results indicate that both Bi _2 O _2 Se and Bi _2 O _2 Te are semiconductors with indirect energy gaps of 0.87 eV and 0.21 eV within spin–orbit coupling, respectively. Large Seebeck coefficient and power factor are found in the p -type than the n -type for both compounds. Low lattice thermal conductivities at room temperature are obtained, 1.14 W m ^−1 K ^−1 for Bi _2 O _2 Se and 0.58 W m ^−1 K ^−1 for Bi _2 O _2 Te, which are close to the experimental values. It is found that the low-frequency optical phonon branches with higher group velocity and longer lifetime also make a main contribution to the lattice thermal conductivity. Interestingly, the lattice thermal conductivity exhibits obvious anisotropy especially for Bi _2 O _2 Te. These results are helpful for the understanding and optimization of thermoelectric performance of layered Bi _2 O _2 Se and Bi _2 O _2 Te.